BS25 Investigating the MIR-101-3P/TRIB1 axis in macrophage immunometabolism. (May 2019) - Niespolo, Chiara; Salamanca Viloria, Juan; Deshmukh, Sumeet; Villacanas Perez, Oscar; Sudbery, Ian; Wilson, Heather; Kiss-Toth, Endre
Abstract : Introduction: MiR-101-3p has been implicated in the regulation of macrophage cholesterol efflux and pro-inflammatory genes by directly targeting ABCA1 and MKP-1, which are both downregulated in atherosclerosis. By using bioinformatic analysis we identified TRIB1 as a direct target of miR-101. The TRIB1 gene plays major roles in myeloid cells, regulating inflammation and lipid metabolism. Its deficiency is associated with a severe reduction of anti-inflammatory tissue macrophages (M2-like cells) and an increase in plasma triglycerides. Here we aimed to uncover the role of miR-101-3p/TRIB1 interaction and its consequences on human macrophage immunometabolism. Methods: MiRanda target prediction algorithm was used to identify macrophage-specific miRNAs targeting TRIB1, along with additional web-based tools. MiR-101-3p was selected based on its conservation among species as well as its high predictive score and free energy. A luciferase reporter assay was used to validate the miR-101-3p/TRIB1 interaction, employing a miR-101 mimic and inhibitor. Gene expression (RT-qPCR) and protein analysis (Western Blot) was carried out in human monocyte-derived macrophages (hMDMs) following transient manipulation of TRIB1 and miR-101 levels. Results: miR-101-3p has a functional binding site for the 3'UTR of TRIB1 and when overexpressed in hMDMs is able to reduce TRIB1 expression at both mRNA and protein levels. Over-expression of TRIB1 in hMDMs alters the levels of pro-inflammatory genes and scavenger receptors, inducing an M2-like phenotype. Conversely, overexpression of miR-101 is associated with a pro-inflammatory phenotype (M1-like). Conclusion: miR-101-3p offers a potential target to simultaneously enhance the expression of ABCA1, MKP-1 and TRIB1, thus improving macrophage lipid metabolism and opposing inflammation, thereby attenuating atherosclerosis development. Conflict of interest: No